2016
DOI: 10.1097/qai.0000000000000897
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Trial to Assess the Safety, Acceptability, Pharmacokinetics, and Pharmacodynamics of a Novel Dapivirine Vaginal Film

Abstract: Background Films may deliver antiretroviral drugs efficiently to mucosal tissues. In this first in-human trial of a vaginal film for delivering the non-nucleoside reverse transcriptase inhibitor dapivirine, safety, pharmacokinetics, and pharmacodynamics of film and gel formulations were compared to placebo. Methods 61 healthy HIV negative women were randomized to daily dapivirine (0.05%) or placebo gel, or dapivirine (1.25mg) or placebo film for seven days. The proportion of participants experiencing Grade 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 29 publications
(30 reference statements)
1
70
0
Order By: Relevance
“…The recently completed phase I trial in women with dapivirine film and gels demonstrated a reduction in the innate anti-HIV activity of cervicovaginal lavage (CVL) fluid samples obtained from the gel users and not the film users (35). It was reported that dilution, due to the greater volume used with gels than with films, could likely account for the reduction in the innate anti-HIV activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recently completed phase I trial in women with dapivirine film and gels demonstrated a reduction in the innate anti-HIV activity of cervicovaginal lavage (CVL) fluid samples obtained from the gel users and not the film users (35). It was reported that dilution, due to the greater volume used with gels than with films, could likely account for the reduction in the innate anti-HIV activity.…”
Section: Discussionmentioning
confidence: 99%
“…This formulation compares well with other film formulation developments, where a dapivirine film showed high PK values in vaginal tissue. Concentrations were detected at levels that can protect against ex vivo HIV infection (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, user acceptance and adherence can be negatively impacted by the leakiness and corresponding untidiness experienced by some users. Similarly, for intravaginal films, user adherence is a common barrier to obtaining efficacy and is impacted by the perceived difficulty of film administration, as well as localized irritation after prolonged contact (76,77). Furthermore, the rapid and complete release of the incorporated agents from intravaginal films within hours of administration may result in transient protection against STIs, thereby remaining a major hurdle to obtaining long-term delivery and efficacy (78,79).…”
Section: Discussionmentioning
confidence: 99%
“…spermicidal film) and lubrication and are under investigation (Ham et al 2012; Akil et al 2014; Zhang et al 2015; Bunge et al 2016) as potential delivery systems for the prevention of sexually transmitted infections, including HIV (Garg et al 2010; Romano et al 2013). Drug delivery is critical, but prevention technology effectiveness ultimately depends on user behaviors.…”
Section: Introductionmentioning
confidence: 99%